"My parents did everything for us but nothing with us": Parenting and mothering in Vietnamese immigrant families in the Czech Republic. (March 2021) - Souralová, Adéla
This article investigates the impact of migration on parent-child ties. It draws upon in-depth interviews with 15 Vietnamese mothers and 20 children (ages 16–25) who either migrated to or were born in the Czech Republic. It asks: How do first-generation mothers and second-generation children make sense of their parents' migration in terms of their relationships with each other? What is the meaning of migration for mothers' and children's comprehension of parenthood and motherhood? The analysis of the interviews illuminates the tensions and ambivalences in narratives about migration and post-migratory situations. The article benefits from the inclusion of two perspectives—mothers' and children's—and contributes to scholarship on family migration, migrant childhood and migrant parenthood.